Perancangan Akses Sistem pYes Automation Tool’s Crib Berbasis Web Server di PT. Astra Otoparts Divisi Winteq - Pusparini Apriningwulan; Ari Santoso; Imam Arifin; Ayyasy Az Zurqi; Moh. Abdul Hady (IPTEK Journal of Proceedings Series, 2019)
PT. Astra Otoparts Winteq Division is an industry engaged in the manufacture of machines with special purpose. Assembling machines using tools such as pliers, screwdrivers, avometers and so forth. These tools will be stored in a place called Tool's Crib, where the operation is done manually with the presence of administrators who serve transactions and bookkeeping is also written conventionally. Bookkeeping of this type causes the information that employees get about the Tool's Crib a bit. Automation Tool's Crib is a tool designed to help with the operation of the Tool's Crib system more effectively with RFID, PLC, applications, databases and web servers. This system also utilizes the application of the internet of things with a website to get information from the machine. This new system can help the administrator work in automated bookkeeping of transactions, so the data in the database can be processed into information in the form of a list of tools that are available on the cabinet, the transaction history of each employee as well as tools that are still borrowed by employees on the website. The management may supervise the transaction and know the condition of the equipment which is also an asset of the company. Tests carried out as many as 50 transactions (borrowing and return) and indicate that changes in data residing on the database can be displayed on the website correctly. All data displayed on the website in each menu is always in accordance with the conditions of the machine.